2014
DOI: 10.1093/gerona/glu022
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D in Relation to Cognitive Impairment, Cerebrospinal Fluid Biomarkers, and Brain Volumes

Abstract: This study suggests that vitamin D may be associated with cognitive status, CSF Aβ(1-42) levels, and brain tissue volumes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
46
1
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(50 citation statements)
references
References 28 publications
2
46
1
1
Order By: Relevance
“…Age-related cognitive decline has been largely explained by the role of vascular pathology [37]. Alternatively, a recent Swedish study reported a positive association between plasma 25(OH)D levels and concentrations of cerebrospinal fluid Aβ 1-42 and brain volumes, which partly accounted for the significant link between reduced plasma 25(OH)D and cognitive impairment [38]. …”
Section: Discussionmentioning
confidence: 99%
“…Age-related cognitive decline has been largely explained by the role of vascular pathology [37]. Alternatively, a recent Swedish study reported a positive association between plasma 25(OH)D levels and concentrations of cerebrospinal fluid Aβ 1-42 and brain volumes, which partly accounted for the significant link between reduced plasma 25(OH)D and cognitive impairment [38]. …”
Section: Discussionmentioning
confidence: 99%
“…A large population based prospective studies of Danish subjects over a follow up period of 30 years has concluded that 25-hydroxy vitamin D3 deficiency increases the risk of AD [181]. Other studies have shown that plasma vitamin D is an important determinant of cognitive status, CSF Aβ42 level and brain volume in patients of AD, MCI and subjective cognitive impairment [182].…”
Section: Vitamin Dmentioning
confidence: 99%
“…Additionally, reduced risk of cognitive impairment, higher concentrations of CSF Aβ1-42 and greater brain volumes (e.g. white matter and structures belonging to medial temporal lobe) were found in patients attending a memory clinic who had higher serum 25(OH)D [8].…”
Section: Surveys Suggest That Up To a Third Of The Populations In Thementioning
confidence: 97%
“…Additionally, reduced risk of cognitive impairment, higher concentrations of CSF Aβ1-42 and greater brain volumes (e.g. white matter and structures belonging to medial temporal lobe) were found in patients attending a memory clinic who had higher serum 25(OH)D [8].A biological rationale for the effect of vitamin D on cognitive performance is plausible. Vitamin D receptors have been located in many brain regions (including the hippocampus) [9] associated with cognitive functions that decline with the development of dementia.…”
mentioning
confidence: 99%
See 1 more Smart Citation